KORELASI SKOR KALSIUM DARI COMPUTED TOMOGRAPHY CALCIUM SCORE DENGAN NILAI FRAKSI EJEKSI VENTRIKEL KIRI DARI ECHOCARDIOGRAPHY - , ESTI ETIKANINGTYAS; , Dr. dr. Lina Choridah, Sp.Rad (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Introduction. Heart Calcium score indicates the amount of calcium in the coronary arteries which can lead to a decrease in cardiac function , as assessed by left ventricular ejection fraction. Ejection fraction is the percentage of blood pumped out of the heart during contraction phase of each heartbeat (systolic). Aims. This study aimed to determine the correlation between calcium score from Computed Tomography Calcium Score with FEVKi from Echocardiography. Material and Methods. This study is a retrospective study with a coss-sectional design. The samples were 54 patients with clinical heart aged 30-65% years who have a performed in the echocardiography examination in the Cardiac Department and Computed Tomography Calcium Score (CTCS) in the Radiology department, Sardjito Hospital, Yogyakarta. The study was conducted in July-August 2014, with data taken from echocardiography and CTCS examination in July 2013 to July 2014. Data were processed with statistical analysis of the correlation (Spearman test) with a significance value of p < 0,05. Results. Calcium scores of 0 = 24 patients (44,4%), 1-10 score = 1 patient (1,8%), 11-100 scores = 17 (31,5%), 101-400 scores = 8 (14,8%) and more than 401 score = 4 patients (7,4%). Normal values of FEVKi (55-75%) = 46 patients (85,2%), normal low or 40-55% = 6 (11,1%) and less than 40% = 2 (3,7%). Spearman correlation test results obtained values of r = - 0,277, p = 0,043. Conclusions. There is a significant negative correlation with weak correlation of strength between calcium scores from CTCS with FEVKi from echocardiography. Keywords: Calcium score, Computed Tomography Calcium Score, FEVKi value, echocardiography